2021
DOI: 10.3390/brainsci11020225
|View full text |Cite
|
Sign up to set email alerts
|

Bliss in and Out of the Body: The (Extra)Corporeal Space Is Impervious to Social Pleasant Touch

Abstract: Slow, gentle stimulation of hairy skin is generally accompanied by hedonic sensations. This phenomenon, also known as (positive) affective touch, is likely to be the basis of affiliative interactions with conspecifics by promoting inter-individual bindings. Previous studies on healthy humans have demonstrated that affective touch can remarkably impact behavior. For instance, by administering the Rubber Hand Illusion (RHI) paradigm, the embodiment of a fake hand enhances after a slow, affective touch compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 97 publications
(190 reference statements)
0
8
1
Order By: Relevance
“…First, in an exploratory study, we tested whether embodied social support (by using affective versus neutral touch 40 ) and social observers, modulate the perception of the space surrounding our body, while also secondarily exploring the role of attachment anxiety. Although we found no evidence of change in PPS after affective touch as compared to neutral touch (as in 51 ), or that such effects were moderated by attachment anxiety, we found that the differentiation between peripersonal and extrapersonal space depended on attachment anxiety and the particular social context. To further investigate this effect, and to exclude that it depended on our tactile manipulations, we conducted a follow-up, preregistered study assessing PPS representation as a function of individual differences in attachment anxiety.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…First, in an exploratory study, we tested whether embodied social support (by using affective versus neutral touch 40 ) and social observers, modulate the perception of the space surrounding our body, while also secondarily exploring the role of attachment anxiety. Although we found no evidence of change in PPS after affective touch as compared to neutral touch (as in 51 ), or that such effects were moderated by attachment anxiety, we found that the differentiation between peripersonal and extrapersonal space depended on attachment anxiety and the particular social context. To further investigate this effect, and to exclude that it depended on our tactile manipulations, we conducted a follow-up, preregistered study assessing PPS representation as a function of individual differences in attachment anxiety.…”
Section: Discussioncontrasting
confidence: 83%
“…The original hypothesis on the role of affective touch in modulating PPS in social context was not confirmed, consistent with previous research that also found no effect of affective versus neutral touch. 51 However, this first exploratory study indicated that the boundaries between peripersonal and extrapersonal space may depend on the combined effects of social context and attachment anxiety, with people scoring higher in attachment anxiety showing a less defined PPS in the presence of a stranger versus alone in comparison to people with lower scores in this dimension.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Nowadays, such findings make sense in terms of affective touch (stroking) leading to greater incorporation of the seen body into the body image. In such cases, note, the type of touch (affective or not) modulates the extent of vision's dominance over proprioception, and thus bodily incorporation (Jenkinson, Papadaki, Besharati, Moro, Gobbetto, Crucianelli, et al, 2020;Panagiotopoulou, Filippetti, Tsakiris, & Fotopoulou, 2017; though see also Spaccasassi, Frigione, & Maravita, 2021).…”
Section: Visual Contributions To Affective Touchmentioning
confidence: 99%
“…Integration of visual and tactile stimuli is enhanced when the visual stimulus is closer to the body rather than far away from it, as revealed by electrophysiological studies in monkey (Graziano, Reiss, & Gross, 1999;Duhamel, Bremmer, Hamed, & Graf, 1997;Fogassi et al, 1996) as well as humans (Noel, Serino, & Wallace, 2019;Bernasconi et al, 2018). In humans, there is also considerable behavioral evidence for multisensory enhancement within PPS (Spaccasassi, Frigione, & Maravita, 2021;Spaccasassi, Romano, & Maravita, 2019;Serino et al, 2015;Brozzoli, Makin, Cardinali, Holmes, & Farnè, 2011;Makin, Holmes, Brozzoli, Rossetti, & Farne, 2009;Làdavas, Pellegrino, Farnè, & Zeloni, 1998).…”
Section: Introductionmentioning
confidence: 99%